Double-outlet left atrium: Ventriculo-atrial malalignment defect - Sudhir S Shetkar; Shyam S Kothari (Wolters Kluwer Medknow Publications, 2013)
A four-month-old female infant presented with heart failure and cyanosis. On echocardiography, there was no outlet to the right atrium except an atrial septal defect and the left atrium drained into the respective ventricles by two atrioventricular valves. The case is reported for its rarity, with a brief literature review.